THE DEAD OF MILD AND MODERATE HEAD INJURY - Musyarrofah Musyarrofah; Abdurahman Wahid; Rismia Agustina (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2018)
The head injury is one of the accidents causing death and disability. Head injuries include in the top 10 most surgical diseases in the Emergency Department of Ulin Hospital Banjarmasin. From January to September 2017, head injured patients amounted to 974 cases. Patients dominated by mild head injury with GCS were 13-15. Patients with head injuries come with severe GCS and some die on the same day of head injury occurrence, but others get intensive care. This research to find out the relationship between GCS on admission and outcome of head injury patient in Emergency Department (ED) of Ulin Hospital Banjarmasin, ED of Idaman Hospital Banjarbaru and ED of Ratu Zalecha Martapura. This research used non-experiment method in cohort way with consecutive sampling for its sample collecting technique from 56 respondents who are the head injury patients in 3 hospital emergency departments. The analysis of relationship between GCS score on admission and outcome of head injury patient using fisher exact test obtained the significance value (2-tailed) of 0.006 < 0.5 which means that H0 is rejected, so there is relationship between GCS score on admission and outcome. The higher the score of GCS on admission, the better outcome received.